The impact of maternal emotional warmth on adolescents’ internalizing problem behaviors: the roles of meaning in life and friendship conflict - Zhang, Ludan; Wang, Ruijie; Li, Yaoyao; Chen, Liang (Frontiers in Psychology, 2024)
Introduction Numerous studies suggest that maternal emotional warmth is a critical protective factor against adolescents’ internalizing problem behaviors. However, the underlying mechanisms linking these variables remain unclear. Grounded in ecological systems theory, this study explores the impact mechanisms of social support (maternal emotional warmth), individual resource (meaning in life), and environmental factor (friendship conflict) on adolescents’ internalizing problem behaviors. Methods A questionnaire survey of 474 adolescents in vocational school aged 15–24 assessed maternal emotional warmth, meaning in life, friendship conflict, and internalizing problem behaviors. Results The results indicate that the meaning in life partially mediates the relationship between maternal emotional warmth and adolescents’ internalizing problem behaviors, with friendship conflict moderating the latter half of this mediation pathway. Discussion The findings suggest that adolescents, during their social adaptation process, activate different protective factors depending on the environmental relational context. Specifically, high friendship conflict limits the direct protective role of maternal emotional warmth, whereas a meaning in life becomes a significant protective factor, exerting its effect through mediation. Conversely, when friendship conflict is low, maternal emotional warmth directly serves as a protective factor.